تفسيرتفهيم القرآن للشيخ أبي الأعلى المودودي في الميزان في ضوء دراسة تفسيرسورتى النساء والمائدة - Arif Mateen; Bashir Ahmad Dars (Pakistan Journal of Islamic Research)
Syed Abul A'ala Maududi (1903-1979), was a major 20th century Muslim thinker, highly distinguished scholar, and revivalist leader. He wrote over 120 books. Maududi’s pen was simultaneously forceful, prolific and versatile. The range of subjects he covered is unusually wide. Disciplines such as Tafsir, Hadith, law, philosophy, politics, history and culture, all have received the due share of his attention. However, his magnum opus is monumental tafsir of the Qur’ān in Urdu namely Tafhim al-Qur’ān, a work that took 30 years to complete. He intended to give the Qur’ān a practical and contemporary interpretation. It became widely read throughout the world and has been translated into several languages of the world. One of its main characteristics lies in presenting the meaning and message of the Qur’ān in a language and style that penetrates the hearts and minds of the men and women of today and shows the relevance of the Qur’ān to their everyday problems, both on the individual and societal levels. He translated the Qur’ān in direct and forceful modern Urdu idiom. He presented the Qur’ān as a book of guidance for whole humanity, as well as a guidebook for the Islamic movements to implement and enforce that guidance in human life. He attempted to explain the verses of the Qur’ān in the context of its total message. This Tafsir has made a far-reaching impact on contemporary Islamic thinking in the Subcontinent, and through its translations, even abroad. The following article is an effort to illuminate some characteristics of his Tafsir as well as some issues and concerns over it, which can be helpful in setting the new paradigms of Tafsir.